Evaluasi Diklat Guru Pendidikan Agama Islam Tingkat SMA - Qowaid Qowaid; Neni Setianingsih (Badan Litbang dan Diklat Kementerian Agama RI, 2006)
Improving the quality of human resources in educational institute becomes one of the priority of government program. the effort is intended for increasing the accessability of society toward qualified educational institution. the article will unpack the establishment of Islamic educational teacher’s trying in a number of religious education and training center. some findings of this research, can functionally be applied for improving the quality of training management in such education and training institutions.